2015
DOI: 10.1038/srep09862
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Pyrazole and its derivative (N-(3-Nitrophenylpyrazole) Curcumin inhibit aggregation, disrupt fibrils and modulate toxicity of Wild type and Mutant α-Synuclein

Abstract: Accumulating evidence suggests that deposition of neurotoxic α-synuclein aggregates in the brain during the development of neurodegenerative diseases like Parkinson’s disease can be curbed by anti-aggregation strategies that either disrupt or eliminate toxic aggregates. Curcumin, a dietary polyphenol exhibits anti-amyloid activity but the use of this polyphenol is limited owing to its instability. As chemical modifications in curcumin confiscate this limitation, such efforts are intensively performed to discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 43 publications
(45 reference statements)
6
82
0
Order By: Relevance
“…There is strong interest in the discovery of small compounds that can act as chemical chaperones modulating the aggregation of α-syn [15,16,17,18,19,20]. In the absence of a defined 3D-structure to target, screening of large collections of chemically diverse compounds is a useful approach toward the discovery of novel bioactive molecules exhibiting an α-syn anti-aggregational effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong interest in the discovery of small compounds that can act as chemical chaperones modulating the aggregation of α-syn [15,16,17,18,19,20]. In the absence of a defined 3D-structure to target, screening of large collections of chemically diverse compounds is a useful approach toward the discovery of novel bioactive molecules exhibiting an α-syn anti-aggregational effect.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical kinetics approaches would allow the quantitative detection of the effects of potential therapeutic molecules on aggregation [21]; however, the application of this type of analysis is hampered by the low reproducibility of aggregation reactions, resulting in dissimilar kinetic parameters and/or high errors even within replicates in the same aggregation assay. This is especially true for α-syn, a protein displaying a very slow aggregation reaction, usually taking several days, which is highly influenced by factors like pH, temperature, agitation or the presence of impurities [18,19,20,22,23,24,25,26,27,28,29,30,31]. The lack of reproducibility between aggregation curves is a strong limitation to identify bona fide aggregation inhibitors, since their potency becomes hidden in overlapping errors bars, especially at the beginning of the reaction, where the more toxic oligomeric species are expected to be formed.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al figured out the biophysical mechanism of Cur on treatment for PD that Cur bound to preformed oligomers and fibrils to prevent aggregation of α-synuclein [16]. Although some researchers highlighted the low bioavailability of curcumin in vivo, which was attributed to limited absorption and metabolic instability [17,18], stable analogs of Cur such as curcumin pyrazole and its derivative N-(3-Nitrophenylpyrazole) curcumin were utilized by Ahsan et al to prevent neurotoxicity in PD along with other neurodegenerative diseases [17]. Ojha et al reported that curcuminoid including curcumin, demethoxy curcumin and bis-demethoxy curcumin relieved dopaminergic neurodegeneration in MPTP-stimulated PD models [19].…”
Section: Discussionmentioning
confidence: 99%
“…Upon addition of CurDAc , a gradual loss in the ThT fluorescence signal was seen, inferring that the population of mature fibrils was diminishing in solution through the disaggregation of hIAPP. A depolymerisation event of α-synuclein has also been seen with curcumin-pyrazole derivatives, 10 alluding to the possible broader scope of CurDAc for disassembling fibrils of other amyloids. The intensity did not equilibrate to the baseline, which may suggest that the small molecule does not disaggregate hIAPP fibers to monomers.…”
mentioning
confidence: 93%
“…68 Curcumin, a natural product found abundantly in turmeric that is used in most south Asian spices, has been widely categorized as having therapeutic properties due to its antioxidant, anti-cancer, antibiotic and anti-amyloidogenic properties. 9 It has been shown to non-specifically bind to amyloid-β monomers and fibrils and modify the protein aggregation pathway; 9,10 but less is known about the interactions between curcumin and hIAPP. Curcumin has demonstrated inhibitory properties against hIAPP; however, its mechanism of action still remains elusive.…”
mentioning
confidence: 99%